SAT0042 TWO POPULATIONS OF PD-1HICD4 T CELLS WITH DISTINCT B CELL HELPING CAPACITY, ARE ELEVATED IN THE PERIPHERAL BLOOD OF PATIENTS WITH EARLY RHEUMATOID ARTHRITIS. (June 2019) - Fortea-Gordo, Paula; Nuño, Laura; Villalva, Alejandro; Peiteado, Diana; Monjo, Irene; Puig-Kröger, Amaya; Sanchez-Mateos, Paloma; Balsa, Alejandro; Miranda-Carus, Maria-Eugenia
Abstract : Background: A novel population of B helper cells, phenotypically CD4+CXCR5-PD-1 hi, has been described in the synovial tissues and peripheral blood of seropositive RA patients with an established disease, and termed 'peripheral helper' (Tph) cells. Contrary to CD4+CXCR5+PD-1 hi follicular helper T (Tfh) cells, Tph cells are not located in lymphoid organs but accumulate in inflamed tissues. The frequency and kinetics of circulating Tph cells have not been examined in patients with early, untreated RA. Objectives: To study the frequency of circulating Tph (cTph) cells, and also of circulating Tfh cell counterparts (cTfh), in patients with early RA (eRA). Methods: Peripheral blood was drawn from DMARD-naïve early RA patients (2010 ACR criteria) with a disease duration < 24 weeks (n=48). For each patient, an age and gender-matched healthy control was also studied (HC, n=48). After isolation by Ficoll-Hypaque gradient, freshly isolated PBMCs were stained with antibodies to CD3, CD4, CXCR5, ICOS, PD-1 and CCR2, and examined by flow cytometry. Autologous cocultures of naïve or memory B cells were established with CXCR5 (+) or (-) memory CD4 T cells. Results: Seropositive (RF+ and/or ACPA+, n=31) but not seronegative eRA patients (n=17), demonstrated increased frequencies and absolute numbers of cTph and cTfh cells. cTph but not cTfh cells expressed CCR2. Those eRA patients who experienced a significant clinical improvement at 12 months, demonstrated a marked reduction of their cTph whereas their cTfh cell numbers remained unchanged; at the same time, rheumatoid factor titres decreased significantly but ACPA (anti-citrullinated peptide antibodies) titres did not vary. Both CXCR5+ and CXCR5-CD4+ T cells were able to induce maturation of memory B cells, whereas only CXCR5+CD4+ T cells could differentiate naïve B cells. Conclusion: Two populations of PD-1 hi CD4 T cells with distinct phenotype and B cell helping capacity, are increased in the peripheral blood of seropositive eRA patients. Whereas cTph are related with disease activity, cTfh cells seem to be constitutively elevated. Reference: [1] Rao DA, et al. Nature2017 Disclosure of Interests: Paula Fortea-Gordo: None declared, Laura Nuño: None declared, Alejandro Villalva: None declared, Diana Peiteado: None declared, Irene Monjo: None declared, Amaya Puig-Kröger: None declared, Paloma Sanchez-Mateos: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Maria-Eugenia Miranda-Carus Grant/research support from: Roche Pharma, BMS